Answer:
HIIIIIIIIIIII
Step-by-step explanation:
Answer:
f(-1) = -1
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
<u>Algebra I</u>
- Functions
- Function Notation
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify</em>
f(x) = 1 - x² + x³
f(-1) is <em>x</em> = -1 for the function f(x)
<u>Step 2: Evaluate</u>
- Substitute in <em>x</em> [Function f(x)]: f(-1) = 1 - (-1)² + (-1)³
- Exponents: f(-1) = 1 - 1 - 1
- Subtract: f(-1) = -1
Answer: 3
Step-by-step explanation: 74 divided by 6 = 12.333